2020
DOI: 10.1177/1942602x20947410
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology in Managing Diabetes in Youth Part 3–Special Considerations: Integration Into the School Setting

Abstract: The advantages of continuous glucose monitoring (CGM) and insulin pump systems have increased the popularity of these devices among students in the school setting. The use of diabetes technology at school and school-sponsored activities strengthens the student’s consistent use of the technology and increases the overall beneficial effects. The school nurse has many considerations when supporting the student with diabetes technology. Integrating this technology into diabetes care at school can be complex with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, access to training tailored to school nurses remains a challenge [11] as options for centralized programs are limited and may rely on access via an organizational membership or diabetes center with the resources to host a training [16,28]. Consistent practice guidelines and educational resources may help to standardize expectations for device use in school [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, access to training tailored to school nurses remains a challenge [11] as options for centralized programs are limited and may rely on access via an organizational membership or diabetes center with the resources to host a training [16,28]. Consistent practice guidelines and educational resources may help to standardize expectations for device use in school [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…52 (19) 41 (15) 66 (25) 65 (24) 46 (17) I recognize when an insulin pump site has failed I can help a student manage their diabetes with a variety of insulin pumps 3.1 ± 1.3 37 (14) 53 (20) 60 (22) 84 (31) 36 (13) I can operate a student's if needed 3.0 ± 1.3 47 (17) 46 (17) 75 (28) 64 (24) 38 (14) I know when to calibrate and when not to calibrate a CGM 2.6 ± 1.3 71 ( 26) 60 (22) 62 (23) 51 (19) 26 (10) I can monitor the CGM tracing/graph when needed 2.9 ± 1.4 60 (22) 54 (20) 66 (24) 42 (16) 48 (18) I can interpret trend arrows on a CGM tracing 3.4 ± 1.4 38 ( 14) 38 ( 14) 56 ( 21) 66 (24) 73 (27) I understand what the diferent CGM alarms mean 3.1 ± 1.4 52 (19) 44 ( 16) 64 (24) 56 (21) 54 (20) I recognize when to test a glucose using a meter for a student with a CGM 3.9 ± 1. a diferent sample using the condensed, 25-item scale only. Our fndings do not imply that device confdence or diabetes knowledge translates to the actual performance of these skills.…”
Section: (35)mentioning
confidence: 99%
“…10 Additionally, the complexity of care in relation to diabetes technologies has increased in both the home and school settings due to the burden of managing the additional equipment, which is always worn on the body. 19 Thus, the integration of the use of diabetes technology into the school setting is essential to ensure effective disease management 20 and to safely meet individualized care needs for long-term wellbeing and optimal academic performance. 4,18,21 Studies have demonstrated the benefits of using diabetes technology in the school setting; a study on the impact of real-time CGM use showed that parents, students, and teachers reported an increase in their ease of managing diabetes in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the complexity of care in relation to diabetes technologies has increased in both the home and school settings due to the burden of managing the additional equipment, which is always worn on the body 19 . Thus, the integration of the use of diabetes technology into the school setting is essential to ensure effective disease management 20 and to safely meet individualized care needs for long-term well-being and optimal academic performance 4,18,21 …”
Section: Introductionmentioning
confidence: 99%